2009
DOI: 10.1007/s00784-009-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Interest in a new test for caries risk in adolescents undergoing orthodontic treatment

Abstract: It has been reported that patients undergoing orthodontic treatment present a high risk of caries. Recently, an immediate chair-side test was proposed, displaying the intra-oral lactic acid production of cariogenic bacteria. The aim of this 12-month follow-up prospective cohort study was to evaluate the association between having a high score on this test and caries occurrence in 110 young patients scheduled for orthodontic treatment. Caries occurrence was studied by Kaplan-Meier curves and Multivariate Cox mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…New approach to the assessment of the cariogenic potential of plaque is focused on the result of fermentation rather than on the identification of one bacterial species or one acid [59]. When the pH of dental plaque is associated with other cariogenic factors, such as DMFT/DMFS index, it becomes a valuable tool for caries risk prediction [60]. In the present investigation, significant influences of both CPP-ACP and CPP-ACFP on plaque pH have been noticed.…”
Section: Discussionmentioning
confidence: 89%
“…New approach to the assessment of the cariogenic potential of plaque is focused on the result of fermentation rather than on the identification of one bacterial species or one acid [59]. When the pH of dental plaque is associated with other cariogenic factors, such as DMFT/DMFS index, it becomes a valuable tool for caries risk prediction [60]. In the present investigation, significant influences of both CPP-ACP and CPP-ACFP on plaque pH have been noticed.…”
Section: Discussionmentioning
confidence: 89%
“…Limited studies were carried out by clinical examinations with various devices such as fluorescence light, 1 DIAGNOdent, 8 an SEM study, 9 and a cariogram study. 10 Some authors 1,8 suggested that orthodontic treatment with a fixed appliance may be compatible with an increased incidence of caries; thus, orthodontists were criticized. Some authors, 9e12 however, found no relationship between fixed orthodontic treatment and caries experience.…”
Section: Discussionmentioning
confidence: 99%
“…To date, clinical detection of WSLs has been carried out primarily by means of traditional methods such as visual inspection with Gorelick index after air drying and tactile examination by dental probing. However, the subjectivity and lack of reproducibility of these approaches, together with the prerequisite of the presence of a significantly advanced lesion, have led to the introduction of several optical techniques during recent decades: the optical caries monitor, use of quantitative laser and light-induced fluorescence, digital imaging with fiber-optic transillumination, laser fluorescence, and computer analysis of digital photographs (14)(15)(16)(17)(18). Because of the nonexistence of these techniques, we consider that visual inspection was appropriate in the present study.…”
Section: Discussionmentioning
confidence: 99%